Sentinel node metastasis mitotic rate (SN-MMR) as a prognostic indicator of rapidly progressing disease in patients with sentinel node-positive melanomas - Baum, Cornelia; Weiß, Christel; Gebhardt, Christoffer; Utikal, Jochen; Marx, Alexander; Koenen, Wolfgang; Géraud, Cyrill (International journal of cancer, 2017)
Risk stratification of sentinel lymph node biopsy (SNB)-positive patients with malignant melanoma differs among current classification systems. To improve classification of patients with rapidly progressive disease who may profit from adjuvant therapy with novel immune or targeted treatment modalities, a single-center retrospective analysis was performed including all melanoma patients diagnosed with a positive SN at a university-based skin cancer center over a 10-year period (2002-2012) (96 of 419 patients). Sentinel node metastasis mitotic rate (SN-MMR) and further histologic parameters were determined by blinded histological re-evaluation and correlated with clinical follow-up (overall [OS], melanoma-specific [MSS], and disease-free survival [DFS]). Median follow-up was 53 months. In univariate analyses, SN tumor penetrative depth (TPD), maximum tumor diameter (MTD), number of positive SN, SN-MMR and the S-, Rotterdam, RDC, Hannover I and II classification systems correlated with OS, MSS and DFS. Multivariate Cox regression analyses showed that a binary classification system based only on the SN-MMR (<1 vs. ≥1 mitoses/mm2) was the strongest independent prognostic indicator for all endpoints analyzed. Kaplan-Meier analyses confirmed binary SN-MMR to be superior to stratify patients into high- and low-risk groups (45.45% vs. 87.92% 5-yr MSS). The general prognostic validity of the published SN classification systems was confirmed. The novel SN-MMR classification system may improve discrimination of patients with slowly and rapidly progressive disease. We therefore propose its implementation into clinical practice as the SN-MMR can be easily and reliably determined in routine pathology reports. Its prognostic value for the selection of patients amenable to adjuvant therapies should be studied in clinical trials.